A prospective randomized study on the efficacy of real-time dynamic navigation in deep horizontal mandibular third molar extractions - Xu Fangfang; Gong Yuxin; Sina Ahmadi; Wang Chunyan; Pouria Arian; Yu Ming; Tu Junbo; Na Sijia (BMC, 2024)
Abstract Purpose This study aimed to evaluate the clinical efficacy of applying real-time dynamic navigation (RDN) in the extraction of deep horizontal mandibular impacted third molars, hypothesizing that RDN reduces surgical time and minimizes the risk of injury to adjacent anatomical structures. Methods A prospective study was conducted on 160 patients aged between 18 and 37 years with deep horizontal impaction of the mandibular third molar. The participants were randomly assigned to either the experimental group (receiving RDN-assisted extractions) or the control group (undergoing traditional extraction methods). Preoperative planning utilized cone beam computed tomography (CBCT) and Mimics software for the accurate localization and segmentation of impacted teeth. Parametric data were analysed via an independent t test for intergroup comparisons, and significance was set to p < 0.05. Results In the experimental group, an average of 11 ± 1 min was required for preoperative planning via RDN, which was not required in the control group. The setup of the navigation system took an average of 4 ± 1 min in the experimental group and 0 min in the control group. The experimental group demonstrated a significantly shorter average surgical time (22 ± 3 min) than did the control group (36 ± 3 min). The differences in the preoperative design time, surgical time, and complication rates between the two groups were statistically significant (p = 0.005). Additionally, the RDN group reported no complications related to adjacent tooth damage or nerve injury. Conclusion The precision, safety, real-time guidance of RDN supports its use in complicated dental extractions, which would introduce a new era of oral and maxillofacial surgery. Graphical Abstract